THE EFFECT OF MUSIC THERAPY ON PAIN LEVEL IN INFUSION IN CHILDREN 6-12 YEARS OF AGE AT HARAPAN DAN DOA HOSPITAL - Yenni Fusfitasari; Kurniawan Saprihadi (Universitas Bengkulu, 2020)
Infusion is an invasive medical procedure that is often performed and causes acute pain and fear in children. Non-pharmacological pain management can be through distraction, one of which is music therapy. The problem in this study is that there are still many complaints of pain in the infusion procedure at Harapan dan Doa Hospital. The purpose of this study was to determine the effect of music therapy on the pain level of infusion in children aged 6-12 years in the Harapan dan Doa Hospital. This type of research is a type of Quasi-Experimental research with a one group design research design. The population is 1305 people and the research sample is 10 people. The type of data used in this research is primary data. Data analysis in this study used univariate and bivariate data analysis with the statistical method of paried sample t test at the 0.05 significance level. The results of this study were the average pain level of patients before being given music therapy was 7.70 and the average pain level of patients after being given music therapy was 5.80. Bivariate Results There is an effect of the effect of music therapy on the pain level of infusion in children aged 6-12 years at Harapan dan Doa Hospital. For officers, it is necessary to improve overall health services, especially regarding non-pharmacological pain intensity management, namely music therapy.